Study of Early Life Cycle of Gourami, Trichogaster spp. with Emphasis the Effect of Temperature, pH and Salinity towards Egg Yolk Absorption and Starvation Period. - Abdul Hakim Azhar (2015)
The present study focuses on early life cycle of Gourami, Trichogaster spp. with emphasis the effect of temperature, pH and salinity towards egg yolk absorption period and starvation period. This study was conducted in order to determine the best environment for rearing gourami fish larvae based on egg yolk absorption and starvation period. Information that obtained from this study can be applied extensive, semi-extensive and intensive farmers to prepare the best condition as one action to reduce the mortality rate at larvae stage. There were three treatments that has been assigned where the gourami fish larvae are placed in different temperature (20°C, 25°C, 30°C), pH (pH 5, pH 6, pH 7, pH 8, pH 9), and salinity (0 ppt, 2 ppt, 4 ppt, 6 ppt, 8 ppt) condition. Thus, results show that there is highly significant value (p<0.05) between the groups of temperature, pH and also salinity towards egg yolk absorption period and starvation period. Based on the temperature, the longest egg yolk absorption period was observed 95 h(s) ± 0.577 in 20°C, compared to 25°C and 30°C which were recorded there is decreased in egg yolk absorption period 73 h(s) ± 0.577 and 47 h(s) ± 0.577 respectively. For starvation period, as the temperature increased, the starvation period becomes shorter. The shortest starvation period recorded is 131 h(s) ± 0.577 in 30°C. Then, there was increase in starvation period for 150 h(s) ± 1.155 and 155 h(s) ± 0.577 in 25°C and 30°C respectively. Based on pH treatment, the longest egg yolk absorption period recorded is pH 7 which 95 h(s) ± 0.667. Then, there was decreased in egg yolk absorption period which recorded, 94 h(s) ± 1.764, 93 h(s) ± 1.155 and 60 h(s) ± 0.577 in pH 8, pH 9 and pH 5 respectively. For starvation period, the data collected showed that there are no significant effect towards the period as the data recorded remain the same from pH 5 to pH 9. Based on salinity treatment, the longest egg yolk absorption period recorded is 94 h(s) ± 1.155 in 0 ppt. There was recorded 70 h(s) ± 0.667 in 2 ppt, 70 h(s) ± 1.155 in 4 ppt. Then, it was fluctuated to 45 h(s) ± 0.667 and 22 h(s) ± 0.667 in 6 ppt and 8 ppt. For starvation period, the longest starvation period recorded was 156 h(s) ± 0.000 in 0 ppt. Then, the period was decreased to 150 h(s) ± 0.667, 96 h(s) ± 0.667, 72 h(s) ± 0.000, and 48 h(s) ± 0.000 for 2 ppt, 4 ppt, 6 ppt and 8 ppt respectively. All of these results obtained were analyzed by using SPSS 16. All the results were highly significant. Thus, based on this study, the best condition for gourami fish larvae rearing are moderate temperature that range 20°C ± 1.0, neutral pH which is pH 7 and low salinity which is 0 ppt. Thus, there is need to study the best condition for gourami fish larvae to grow as the present study only cover with early life cycle.